2013
DOI: 10.1155/2013/134694
|View full text |Cite
|
Sign up to set email alerts
|

The Hypocholesterolemic Effect of Germinated Brown Rice Involves the Upregulation of the Apolipoprotein A1 and Low-Density Lipoprotein Receptor Genes

Abstract: Germinated brown rice (GBR) is rich in bioactive compounds, which confer GBR with many functional properties. Evidence of its hypocholesterolemic effects is emerging, but the exact mechanisms of action and bioactive compounds involved have not been fully documented. Using type 2 diabetic rats, we studied the effects of white rice, GBR, and brown rice (BR) on lipid profile and on the regulation of selected genes involved in cholesterol metabolism. Our results showed that the upregulation of apolipoprotein A1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…They showed that total cholesterol in rats fed with high-cholesterol diets is reduced to a greater extent by brown rice when sprouted for 2 days, than by such rice either nonsprouted or sprouted for just 1 day. Imam et al (2013), with an in vivo rat study, showed that, although the effects on total cholesterol were similar for brown rice and sprouted brown rice, the lipid composition was more favorable for decreasing the CVD risk after consumption of the latter. A corrective effect on hypercholesterolemia of (sprouted) brown rice was observed with hepatoma-bearing rats by Miura et al (2006).…”
Section: Lipid Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…They showed that total cholesterol in rats fed with high-cholesterol diets is reduced to a greater extent by brown rice when sprouted for 2 days, than by such rice either nonsprouted or sprouted for just 1 day. Imam et al (2013), with an in vivo rat study, showed that, although the effects on total cholesterol were similar for brown rice and sprouted brown rice, the lipid composition was more favorable for decreasing the CVD risk after consumption of the latter. A corrective effect on hypercholesterolemia of (sprouted) brown rice was observed with hepatoma-bearing rats by Miura et al (2006).…”
Section: Lipid Metabolismmentioning
confidence: 97%
“…The main grains used were rice (six in rodents, one in humans) and barley (three in rodents, one in humans) with, to the best of our knowledge, wheat, millet, and oats each used in only one (human) study. Brown rice has been used by various researchers to investigate the effect of sprouting on lipid metabolism or symptoms linked to it (Imam et al., ; Imam, Ismail, Omar, & Ithnin, ; Miura et al., ; Roohinejad et al., ; Wu, Yang, Touré, Jin, & Xu, ). However, the sprouting conditions used differed from one study to another and so did the levels of bioactive compounds such as tocopherol, oryzanol, and GABA (Miura et al., ; Roohinejad et al., ).…”
Section: Health Benefits Of Sprouted Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatic LDL-R (receptor) clears up LDL-C from the blood circulation, thus indicating an increased expression of LDL-R would be favorable for the increased elimination of LDL-C. The bioactive compounds of GBR, such as phytosterols, GABA, oryzanol and phenolics have previously been ascribed to the up-regulation of LDL-R gene in HEPG2 cells (15,16). Other reports also support that GBR causes upregulation of both apoA-1 and LDL-R genes (17).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on type 2 diabetic rats has shown that germinated brown rice exerts a hypocholesterolemic effect involving the upregulation of apolipoprotein A1 and of LDL receptor genes (Imam, Ismail et al 2013). An ethyl acetate extract from brown rice, evaluated in vitro on rat smooth muscle cells, has hindered the stimulatory effect of angiotensin II, suggesting antihypertensive properties (Utsunomiya, Takaguri et al 2011).…”
Section: Hypercholesterolemia and Cardiovascular Diseasementioning
confidence: 99%